The Emerging Potential of Parthenolide Nanoformulations in Tumor Therapy - An T; Yin H; Lu Y; Liu F (Dove Medical Press, 2022)
Tao An,1 Huanhuan Yin,1 Yanting Lu,2 Feng Liu1,3 1School of Pharmaceutical Sciences, Qilu University of Technology (Shandong Academy of Sciences), Jinan, Shandong Province, People's Republic of China; 2College of TCM, Shandong University of Traditional Chinese Medicine, Jinan, Shandong Province, People's Republic of China; 3Key Laboratory for Applied Technology of Sophisticated Analytical Instruments of Shandong Province, Shandong Analysis and Test Center (SDATC), Qilu University of Technology (Shandong Academy of Sciences), Jinan, Shandong Province, People's Republic of ChinaCorrespondence: Feng Liu, Key Laboratory for Applied Technology of Sophisticated Analytical Instruments of Shandong Province, Shandong Analysis and Test Center (SDATC), Qilu University of Technology (Shandong Academy of Sciences), 19th Keyuan Road, Jinan, 250014, Shandong Province, People's Republic of China, Tel +86 531-82605319, Fax +86 531-82964889, Email liufeng8109@163.comAbstract: Plant-derived sesquiterpene lactones are promising natural sources for the discovery of anti-cancer drugs. As an extensively studied sesquiterpene lactone, the tumor suppression effect of parthenolide (PTL) has been clarified by targeting a number of prominent signaling pathways and key protein regulators in carcinogenesis. Notably, PTL was also the first small molecule reported to eradicate cancer stem cells. Nevertheless, the clinical application of PTL as an antitumor agent remains limited, owing to some disadvantages such as low water solubility and poor bioavailability. Thus, nanomedicine has attracted much interest because of its great potential for transporting poorly soluble drugs to desired body sites. In view of the significant advantages over their free small-molecule counterparts, nanoparticle delivery systems appear to be a potential solution for addressing the delivery of hydrophobic drugs, including PTL. In this review, we summarized the key anticancer mechanisms underlined by PTL as well as engineered PTL nanoparticles synthesized to date. Therefore, PTL nanoformulations could be an alternative strategy to maximize the therapeutic value of PTL.Graphical Abstract: Keywords: parthenolide, signaling pathways, cellular processes, nanomedicine, cancer therapy